Implementasi Model Problem-Based Learning (PBL) untuk Meningkatkan Berpikir Kritis Siswa: Studi Kasus SMA Ma’arif Lawang - Ahmad Mahendra Pratama; Yuli Ifana Sari (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
This study aims to describe the implementation of the Problem-Based Learning (PBL) model in remote sensing material to improve students’ critical thinking skills at SMA Ma’arif Lawang. The research employed a descriptive qualitative approach with a case study method, involving tenth-grade students and geography teachers as key informants. Data were collected through structured interviews, participatory observation, and documentation, then analyzed using Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that PBL enhances student engagement in learning, encourages independent questioning, and strengthens the understanding of abstract concepts in remote sensing through group discussions and project-based activities. The main challenge faced by students was the limited experience in interpreting satellite imagery, which was overcome through teacher guidance and peer collaboration. Overall, PBL proved effective in bridging abstract concepts with real-life experiences, making geography learning more contextual, participatory, and aligned with the goals of the Merdeka Curriculum. This study contributes to the development of innovative learning strategies relevant to fostering students’ critical thinking skills in the 21st century.